Efek Hipoglikemik Ekstrak Etanol Bonggol Nanas (Ananas comosus (L.) Merr) Pada Mencit Putih Jantan yang diinduksi Aloksan - Viko Duvadilan Wibowo; Tri Wahyu Hidayat; Masayu Azizah (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2021)
Diabetes mellitus is one of ten diseases that cause death in adults and other causes of complications, one of which is characterized by hyperglycemia. Currently, people prefer to use herbal remedies to treat their ailments, including pineapple stem as an alternative to diabetes treatment. This research was conducted on 25 male white mice swiss webster strain aged 2-3 months with a weight of approximately 20-30 grams. Mice were randomly divided into five groups, namely KN (negative control/tween 80 1%), KP (positive control/metformin 65 mg/kgBW), EB1 (ethanol extract of pineapple stem 125 mg/kgBW), EB2 (ethanol extract of pineapple stem 250 mg/kgBW), EB3 (ethanol extract of pineapple stem 500 mg/kgBW). Mice were induced with alloxan at a dose of 150 mg/kgBW intraperitoneally. Each group was given a test preparation for 14 days, where on the 3rd, 7th, and 14th day the mice’s blood was taken to check their fasting blood glucose levels using a digital glucometer. The results of this study indicated that all groups of pineapple stem test were efficacious in reducing fasting blood glucose levels of mice on the 14th day. The EB2 group showed an increase in the mean percent decrease in fasting blood glucose level which was not significantly different (p <0.05) with the metformin group, even though metformin was still superior. The EB1 and EB3 groups also showed an increase in mean percent decrease in blood glucose levels, but they were not significantly different from the negative control group.